2022
DOI: 10.3390/ijerph192315911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Reality-Based Graded Exposure Therapy on PTSD Symptoms: A Systematic Review and Meta-Analysis

Abstract: Previous studies reported that virtual reality (VR)-based exposure therapy (VRET) was a clinically beneficial intervention for specific phobias. However, among VRET, VR-based graded exposure therapy (VR-GET) is little known about its efficacy on posttraumatic stress disorder (PTSD) symptoms. Therefore, this meta-analysis investigated the effects of VR-GET for PTSD symptoms. A literature search yielded seven randomized controlled trials. The differences between conditions regarding the primary outcome of PTSD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
(72 reference statements)
0
4
1
1
Order By: Relevance
“…Recent meta-analyses and systematic literature reviews suggest that VRET exhibits comparable efficacy to traditional imaginal exposure therapies for PTSD treatment ( Deng et al, 2019 ; Kothgassner et al, 2019 ; Heo and Park, 2022 ). However, there is no evidence to suggest that VRET outperforms other exposure methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analyses and systematic literature reviews suggest that VRET exhibits comparable efficacy to traditional imaginal exposure therapies for PTSD treatment ( Deng et al, 2019 ; Kothgassner et al, 2019 ; Heo and Park, 2022 ). However, there is no evidence to suggest that VRET outperforms other exposure methods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether VRET is a better alternative becomes a matter of cost-effectiveness. Nonetheless, VRET can be considered a viable option for those who struggle with envisioning traumas ( Heo and Park, 2022 ). Customizing software for each client is a time-consuming and potentially cost-ineffective process.…”
Section: Introductionmentioning
confidence: 99%
“…VR can be used in treatments that concentrate on pain management and relaxation 15 16. VR-based exposure therapy has also been shown as helpful for patients with psychiatric problems such as anxiety, phobias and post-traumatic stress disorder 17–19. In addition, according to recent systematic reviews, VR has the potential to improve depression in adults and older individuals20 21; one study found VR may enhance the clinical efficacy of behavioural activation for depression in adults 22.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR) is a practical technology that combines virtualisation and reality to create a digital environment that is similar to the real environment [ 23 ]. Over the past 20 years, VR has been widely used in the study of a variety of mental disorders, such as anxiety disorders [ 24 ] (especially phobias) [ 25 , 26 ], post-traumatic stress disorder [ 27 , 28 ], substance use disorders [ 29 , 30 ], gambling disorders [ 31 , 32 ], eating disorders [ 33 , 34 ], and autism spectrum disorders [ 35 , 36 ]. Virtual reality-based cue exposure therapy (VR-CET) has significant advantages, as VR can not only create more realistic life scene through multiple sensory inputs such as vision, auditory, smell, or touch, but also provide multiple cues for exposure simultaneously, increasing the the realism and immersion of exposure.…”
Section: Introductionmentioning
confidence: 99%